Light-exposure at night impairs mouse ovary development via cell apoptosis and DNA damage. Issue 5 (2nd May 2019) - Li, Yapeng; Cheng, Shunfeng; Li, Lan; Zhao, Yong; Shen, Wei; Sun, Xiaofeng
Abstract : The alternation of light and dark rhythm causes a series of physiological, biochemical and metabolic changes in animals, which also alters the growth and development of animals, and feeding, migration, reproduction and other behavioral activities. In recent years, many studies have reported the effects of long-term (more than 6 weeks) illumination on ovarian growth and development. In the present study, we observed the damage, repair and apoptosis of ovarian DNA in a short period of illumination. The results showed that, in short time (less than 2 weeks) illumination conditions, the 24-h light treatment caused the reduction of total ovarian follicle number and down-regulation of circadian clock related genes. Furthermore, the changed levels of serum sex hormones were also detected after 24-h light exposure, of which the concentrations of LH (luteinizing hormone), FSH (follicle-stimulating hormone) and E2 (estradiol) were increased, but the concentration of PROG (progesterone) was decreased. Moreover, 24-h light exposure increased the expression of DNA damage and repair related genes, the number of TUNEL and RAD51 positive cells. These results indicated that 24-h light exposure for 4, 8 and 12 days increased DNA damage and cell apoptosis, thereby affecting the development of ovary.